Correlation Between Vocabulary Mastery And Writing Ability Of The Fourth Semester Students Of English Study Program Of Fkip Universitas Nahdlatul Ulama Lampung - Aulfa Reyza Ayuni Prestika (Journal on Education, 2024)
This research is aimed to find out the significant correlation between vocabulary mastery and writing ability of the fourth semester students of English Study Program FKIP Universitas Nahdlatul Ulama Lampung. The sample of this research was class A, consist of 13 students. The data were collected using two kinds of test; first test is a vocabulary test and the second is writing test. The result of this research showed the fourth semester students of English Study Program FKIP Universitas Nahdlatul Ulama achieved good level in both with the average score 73 in vocabulary and 77 in writing. The result of this research proved that there was a positive correlation between the vocabulary mastery and writing ability of the fourth semester students of English Study Program FKIP Universitas Nahdlatul Ulama Lampung. The Rxy distribution of the coefficient correlation was 0.661. It means that there was a high correlation between vocabulary mastery and writing ability of the fourth semester students of English Study Program FKIP Universitas Nahdlatul Ulama Lampung. Therefore, alternative hypothesis (Hα) was accepted and the null hypothesis (Ho) was rejected.